Legally Speaking: Oracle v. Google: Are APIs Copyrightable? - Samuelson, Pamela (Communications of the ACM, 2012)
The article discusses a U.S. intellectual property lawsuit between the computer companies Oracle Corp. and Google Inc. concerning the copyright of application program interfaces, arguing that the May, 2012 ruling in favor of Google will be upheld. Topics include the Java computer programming language, the acquisition of the computer company Sun Microsystems by Oracle, and previous electronic copyright court decisions.